A Survey on Service Oriented Scheduling for Big Data Cloud - Srinath, R; Biradar, Arun (International Journal of Computer Sciences and Engineering, 2025)
Big Data is an emerging data intensive computing technology to extract intrinsic information from large scale variety forms of rapidly growing data. Big Data Analytics is a data science paradigm, which employs several statistical and machine learning tools for effective and quick decision making. As Cloud computing technologies are coming into reality, several Cloud providers are offering large scale computing and storage facilities as services based on pay and consumption models to the end users. Due, to their service oriented delivery of Clouds, these are turning as back end infrastructure to address several big data mining problems in Big Data computing. As the convergence of Clouds and Big Data is turning into new area aka “Big Data Clouds”, there is a need to address several under pinning technical elements of Big Data computing in Clouds. In this paper, we discuss Service oriented scheduling mechanisms to serve Big Data Analytics in Clouds infrastructure as services. Our main focus is on scheduling aspects, which bring out the several issues, thus meeting the constraints, and Quality of Service (QoS) parameters. We initially, bring about several challenges in scheduling the Big Data problems over Clouds infrastructure, followed by offering the service oriented analytics deliver over Clouds based SLAs and the Quality of Service while considering the dead line, budget constraints.